pH and calcium ion release evaluation of pure and calcium hydroxide-containing Epiphany for use in retrograde filling - Tanomaru-Filho, Mario [UNESP]; Sacaki, Juliana Nogueira; Chaves Faleiros, Frederico Bordini [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2011)
Objective: Hydroxyl (OH(-)) and calcium (Ca(++)) ion release was evaluated in six materials: G1) Sealer 26, G2) White mineral trioxide aggregate (MTA), G3) Epiphany, G4) Epiphany + 10% calcium hydroxide (CH), G5) Epiphany + 20% CH, and G6) zinc oxide and eugenol. Material and Methods: Specimens were placed in polyethylene tubes and immersed in distilled water. After 3, 6, 12, 24, and 48 h, 7, 14, and 28 days, the water was assessed for pH with a pH meter and for Ca++ release by atomic absorption spectrophotometry. Results: G1, G2, G4, and G5 had the highest pH until 14 days (p < 0.05). G1 presented the highest Ca(++) release until 6 h, and G4 and G5, from 12 h through 14 days. Ca(++) release was greater for G1 and G2 at 28 days. G6 released the least Ca(++). Conclusions: MTA, Sealer 26, Epiphany, and Epiphany + CH release OH-and Ca(++) ions. Epiphany + CH may be an alternative as retrofilling material.
Keywords: Retrograde obturation; Hydrogen-ion concentration; Calcium hydroxide